KAJIAN CYBER SECURITY DALAM RANGKA KOPERASI MENGHADAPI REVOLUSI INDUSTRI 4.0 - Kuncoro Wibowo; Udin Hidayat; Verdi Yasin (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2023)
Cyber Security is an effort to protect information from Cyber Attacks. The purpose of making this paper is to inform the importance of Cyber Security in application devices, software and other devices in the era of the industrial revolution 4.0. For example, in Android Cyber Security is very important because to protect the information that we have and this cyber security is widely used by corporate companies as well. In accordance with the discussion above, it can be concluded that Cyber Security in the era of the industrial revolution 4.0, why is that? Because Cyber Security itself is designed and made to overcome problems that might occur in the cyber world, its use is very useful, guaranteed and feasible to use even for the cyber security system itself to develop and continue to get better with time. then there is no doubt about the security, comfort and usefulness of the cyber security itself. Keywords: Cyber Security, Applications, Software, Industrial Revolution